Omega-3 fatty acids supplementation improves endothelial function and maximal oxygen uptake in endurance-trained athletes - Zebrowska, A.; Mizia-Stec, K.; Mizia, M.; Gasior, Z.; Poprzecki, S. (European Journal of Sport Science, 2015)
The study aimed to evaluate the effects of a 3-week n-3 polyunsaturated fatty acids (n-3 PUFA) supplementation on serum nitric oxide (NO), asymmetric dimethyloarginine (ADMA), ultrasound indices of endothelial function and maximal oxygen uptake (VO2max) of elite cyclists. The effects of dietary supplementation (n-3 PUFA at a dose of 1.3 g twice daily for 3 weeks) and placebo administration on flow-mediated dilatation (FMD), pulse wave velocity, serum markers (NO, ADMA), lipid profile, and Delta VO2max were analysed in 13 cyclists both before and after dietary protocols. Significant differences between pre- and post-intervention baseline NO levels were observed after n-3 PUFA dietary protocol (13.9 ± 4.2 vs. 23.5 ± 3.6 µmol·l-1; P < 0.001). Higher post-intervention baseline NO level was observed after n-3 PUFA diet compared with placebo (23.5 ± 3.6 vs. 15.3 ± 3.0 µmol·l -1; P < 0.01, respectively). The n-3 PUFA increased baseline NO concentration (Delta NO) by 6.7 ± 3.8 µmol·l-1 and placebo by 1.6 ± 4.4 µmol·l-1. The positive correlation was observed between baseline post-intervention NO concentration and maximal oxygen uptake (r = 0.72; P < 0.01) and also between Delta NO and Delta VO2max (r = 0.54; P < 0.05) in response to omega-3 fatty acids supplementation. There was an association between a 5.25% higher FMD (P < 0.05) and higher (P < 0.001) after n-3 PUFA diet compared with lower values of placebo (r = 0.68; P < 0.05). These findings suggest that an increase in NO release in response to n-3 PUFA supplementation may play a central role in cardiovascular adaptive mechanisms and enhanced exercise performance in cyclists.